DERIVATIONAL MORPHEMES IN OPINION COLUMNS OF ONLINE NEWSPAPER: REUTERS - Heryanto, Edi; Rosmaidar, Rosmaidar (Jurnal Ilmiah Bina Bahasa, 2017)
Abstract: The objectives of this study were to find out derivational morphemes used in the articles of Reuters, their types and patterns. Descriptive approach was used in this study. Greenbaum?s and Fromkin?s theory were used in finding the types and the patterns of derivational morphemes. The result of the study showed that the constructions of verb bases are used to create noun forms especially abstract nouns. There were 235 types of derivational morphemes: 35 (14.89%) were prefixes and 200 (85.10%) were suffixes. Types of prefixes were supportive and opposing, reservative and deprivative, negative, pejorative, place, time, status, number, and miscellaneous prefixes. The types of suffixes were verb, adjective, concrete nouns, abstract nouns, and adverb suffixes. There were 221 patterns of derived words found in the study.   Keywords: Morphology, Derivational Morphemes, and Reuters.   Abstrak: Tujuan dari penelitian ini adalah untuk menemukan jenis dari morfem derivasional yang digunakan pada artikel koran online Reuter, dan pola mereka. Metode kualitatif dengan pendekatan deskriptif digunakan pada penilitian ini. Teori Greenbaum dan Fromkin digunakan untuk mengetahui jenis dan pola morfem derivasional. Hasil penelitian menunjukkan bahwa kata kerja dasar digunakan untuk membentuk kata benda, khususnya nomina abstrak. Ada 235 jenis morfem derivasional yang ditemukan. 35 (14.89%) adalah prefiks dan 200 (85.10%) adalah sufiks. Jenis prefiks mencakup prefiks berlawanan dan suportif, deprivasi dan kebalikan, negatif, pejoratif, kedudukan, waktu, status, angka, campuran. Sedangkan, jenis sufiks mencakup sufiks kata kerja, kata sifat, nomina konkrit, nomina abstrak, dan kata keterangan. Ada 221 pola kata imbuhan derivasi di ketahui di dalam penilitian.   Kanta kunci: Morfologi, Morfem Derivasional, dan Reuters.